Value Chain Model Development of Tuna and Tuna Alike In Indonesia - Ateng Supriatna; Budi Hascaryo; Sugeng Hari Wisudo; Mulyono S Baskoro (Jurnal Pengolahan Hasil Perikanan Indonesia, 2014)
Sustainability of tuna and tuna alike fisheries depend on chain value system formed by stakeholders ranging from product fishing, processing/diversification, distribution, and marketing. The objective of this research was to create chain value system model of tuna and tuna alike fisheries, to predict the interaction pattern of stakeholders and to formulate the precise strategy to minimize the synergy resistance of chain value system development strategy of tuna and tuna alike fisheries. Structural Equation Modelling (SEM) was applied to analyze the chain value model. The stakeholders/the players of tuna and tuna alike fisheries basically have positive interaction (CE>0).The negative interaction occured on retailers and consumers. Interaction of retailers with consumers is significant (p<0.05) 0.01. Interaction pattern of fishermen, retailers, collectors, and exporters affected significantlly by pricing and the level of role played by the stakeholders. The strategy to minimize the sinergy resistance of chain value system development are respectivelly the strategy of involving the group of fishermen on products pricing (CE= 1,176 and P= 0,000), the strategy of involving the seller groups on products pricing (CE-PE=1,08, CE-PB= 0,766, CE EKS= 2,028 AND P= 0,000), and the strategy on guaranteeing flexible interaction between retailer and consumers (CE= 0,179 and p = 0,01).Keywords: tuna and tuna alike, interaction, tuna and tuna alike stakeholders, and value chain